A method for preparing a diamond-nickel superhard material with metallic-grade conductivity

By constructing conductive paths in nanodiamonds, combined with foam nickel foam and high temperature and high pressure technology, diamond-nickel superhard conductive composite materials with good hardness and good conductivity were prepared, which solved the problem of insufficient performance of conductive materials under extreme conditions in the prior art.

CN119553125BActive Publication Date: 2025-04-15JILIN UNIVERSITY +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510114606.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-24
Publication Date
2025-04-15
Estimated Expiration
2045-01-24

AI Technical Summary

Technical Problem

It is difficult for existing conductive materials to meet the requirements of high compressive strength, tensile strength, wear resistance and hardness under extreme conditions, and at the same time, conductivity and super hardness are difficult to take into account.

Method used

Mesh-shaped nickel foam and nanodiamond powder are mixed in proportion, and conductive paths are constructed in nanopolycrystalline diamonds through ultrasonic filling and high-temperature and high-pressure sintering technology to form ultra-hard conductive composite materials.

Benefits of technology

The conductivity and superhardness of metal magnitude are achieved, with a hardness of more than 80 GPa and an resistivity of one order of magnitude lower than metal, solving the problem of low hardness of traditional conductive materials and poor conductivity of superhard materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119553125B_ABST
    Figure CN119553125B_ABST
Patent Text Reader

Abstract

The present invention relates to a method for preparing a diamond-nickel superhard material with metal-level conductivity, which belongs to the technical field of preparing superhard conductive composite materials. Nano-sized diamond and nickel foam are used as raw materials, and an ultrasonic method is used for mixing. A pretreatment process is introduced at the same time. Under the conditions of 5 GPa, 700-2000°C insulation time of 20 min, the surface of the nano-diamond filled in the pores of the nickel foam is graphitized, a nickel atom diffusion channel is provided, and the nickel foam skeleton is refined so that nickel atoms diffuse along the diamond surface graphite layer. Then, sintering is performed under the conditions of 10-20 GPa 1800°C insulation for 20 min to obtain a superhard and metal-level conductive diamond-nickel composite material. The present invention prepares a superhard conductive composite material with conductivity close to that of metal by constructing a conductive path and utilizing the diffusion rate of nickel atoms in graphite to be much higher than the diffusion mechanism of diamond.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of metal composite material preparation, and specifically relates to a method for preparing a superhard conductive composite block material based on nano-diamond and using foamed nickel as a conductive phase. Ultrasonic filling combined with high temperature and high pressure sintering technology is used to construct a conductive path in nano-polycrystalline diamond to achieve superhard conductivity of the composite material. Background Art

[0002] With the development of science and technology, the exploration of extreme conditions has become a hot area of ​​current research. These extreme environments put forward higher requirements on the mechanical properties of conductive materials, such as higher compressive strength, tensile strength, wear resistance and hardness, to meet the requirements of long-term stable service in extreme environments. However, the current excellent conductive materials are mostly metals or alloy materials, which have good conductivity (according to the current national standard: GB / T 351-2019 metal material resistivity is 1*10 -8 ~2*10 -6 Ω·m), but its hardness is generally low; materials with superhard properties (HV>40 GPa) are generally non-metallic materials and insulators. Therefore, it is particularly important to develop a composite material that couples superhard properties and conductive properties.

[0003] Diamond is the hardest material currently available, and also has good thermal conductivity, wear resistance, and excellent chemical stability. sp 3Hybridized covalent bonds, strong covalent bonds cause its electrons to be localized near the carbon atom, making diamond insulating. Although current studies have shown that diamond conductivity can be achieved by doping B, its conductivity is only at the semiconductor level. At the same time, the difficulty of doping and the low doping concentration also restrict the application of B-doped diamond in the field of conductor materials. Therefore, compared with doping to improve the conductivity of diamond, it is more feasible to prepare diamond conductive composite materials by composite conductive second phase. The Chinese patent with authorization announcement number CN 114231817 B provides a composite material with a hardness of more than 40 GPa and conductivity prepared by cBN and metals and ceramics (Ni, Ti, TiN, Co, TiC) under sintering pressure (5.5-7.5 GPa) and sintering temperature (1250-1750 ℃). It shows that choosing the right strategy is expected to prepare composite materials that are both superhard and conductive. Due to the high interfacial energy of diamond, diamond powder is difficult to sinter. Metal binders are added during the sintering process of traditional polycrystalline diamond (PCD) to improve sinterability. Although polycrystalline diamond has a hardness higher than 40 GPa and has a certain conductivity, its conductivity is much lower than that of metal. The literature "Investigation on material property of electrically conductive polycrystalline composite diamond (EC-PCD)" (Advanced Materials Research 2010 Vol.126-128 Pages 639-644) reported that polycrystalline diamond prepared by high temperature and high pressure method with 10 mol% cobalt as binder and the rest as diamond had a resistivity of 5.34*10 -4 Ω·m is two orders of magnitude lower than that of metal. In addition, according to the literature "Centimeter-sized diamond composites with high electrical conductivity and hardness" (Proceedings of the National Academy of Sciences of the United States of America 2024 Vol. 121 No.9 Pagese2316580121), a method for preparing diamond-graphite superhard conductive composite materials using nanodiamond as a precursor by high temperature and high pressure method was reported. It precisely controls the temperature and pressure conditions, and then controls the degree of graphitization on the surface of nanodiamond, so that graphite conductive paths are formed between nanodiamond particles to achieve superhard conductivity of the material, and its conductivity is also one order of magnitude lower than that of metal (HV= 55.8 GPa conductivity: 5.0*10 -5Ω·m). However, due to the low intrinsic hardness of graphite and the poor lattice matching between diamond and graphite, the hardness of the composite material is much lower than that of diamond. Therefore, previous work can only prepare superhard conductive materials with a hardness of less than 60 GPa, and there are no reports on extremely hard (HV>80 GPa) conductive materials. The fundamental reason is that when the composite phase is prepared, the conductive phase is easy to aggregate, resulting in the cutting of the conductive path, which reduces the conductivity of the material. How to maintain a good conductive path is the key to preparing extremely hard conductive materials.

[0004] In view of the above-mentioned difficult problems, the present invention adopts the method of filling diamonds inside the grid-like nickel foam pores, and pre-constructs a conductive network inside the sintered nano-diamond. At the same time, a pretreatment process is designed to pre-graphitize the surface of the nano-diamond filled in the nickel foam grid to construct a nickel diffusion path. Since the diffusion speed of nickel atoms in graphite is much higher than that of diamonds, nickel atoms can diffuse to the gaps between diamond particles along the graphite layer between diamond particles, making the conductive path more evenly distributed. At the same time, nickel can promote the transformation of graphite to diamond as a catalyst, and promote the transformation of graphite between diamond particles to diamond under appropriate pressure. The rapid transformation of graphite causes the nickel localization in the graphite layer to form a conductive path between diamond particles. Thus, the present invention constructs a conductive nickel path network inside the sintered nano-diamond, obtains a diamond-nickel bulk material with metallic conductivity, realizes the coupling of superhardness and high conductivity in diamond-nickel composite materials, and provides a new idea for the preparation of conductive diamond. Summary of the invention

[0005] In order to overcome the shortcomings of the background technology and meet the new demand for the application of conductive materials under extreme conditions, the present invention adopts a skeleton-connected foam nickel and nano-diamond powder mixed in proportion, and adopts a high temperature and high pressure method to prepare a diamond-nickel superhard conductive composite material.

[0006] The specific technical solutions of the present invention are as follows:

[0007] A method for preparing a metallic-grade conductive diamond-nickel superhard material comprises the following steps:

[0008] 1) Ingredients: First weigh the nickel foam, then put nanodiamonds with a particle size of 30-50 nm and nickel foams with a diameter of 2 mm and an average pore size of 150 μm into anhydrous ethanol for ultrasonic mixing to obtain a nickel foam mixed block filled with diamond; wherein the molar ratio of nanodiamonds is 93-97%, and the remainder is nickel foam; the mass ratio of nanodiamonds to anhydrous ethanol is 1:9; the ultrasonic frequency is 40 kHz and the ultrasonic time is 30 min;

[0009] 2) Drying treatment: Place the nickel foam filled with nanodiamonds with a diameter of 2 mm in a drying oven and dry it at 100°C for 120 min to remove the anhydrous ethanol, and then weigh it;

[0010] 3) Pre-pressing treatment: the dried nickel foam is placed in an assembly block, and then placed in a six-sided hydraulic press for pre-pressing at a pressure of 5 GPa, a temperature of 700 ℃ to 2000 ℃, and a heat preservation and pressure holding time of 20 min, and then the pressure is released to obtain a pre-pressed sample with a diameter of 1.5 mm and a height of 2 mm;

[0011] 4) Sample preparation: The pre-pressed sample was placed in a Kawaii 68 press and sintered at a pressure of 10-20 GPa and a temperature of 1800 °C for 20 min. The sample was then cooled and depressurized to obtain a diamond-nickel superhard material with metallic-grade conductivity.

[0012] Preferably, in the diamond-filled nickel foam mixed block described in step 1), the nickel foam accounts for 5% of the total sample molar weight.

[0013] Preferably, the pre-pressing treatment conditions in step 3) are 5 GPa, 1800°C, and 20 min. The diamond surface is graphitized by the pre-pressing treatment, and nickel is diffused into the graphite, thereby obtaining a pre-pressed sample having a structure of diamond / graphite / nickel from the inside to the outside.

[0014] Preferably, the six-sided hydraulic press model described in step 3) is CS-Ⅲ*614000. Beneficial Effects

[0015] In the present invention, during the pretreatment process of 5 GPa, 700 ℃ to 2000 ℃, and the heat preservation and pressure holding time of 20 min, the diamond surface is graphitized. Therefore, the graphitization of the nano-diamond surface can be used as a nickel diffusion channel, the nickel skeleton of the foamed nickel and the nickel diffused between the diamond particles can be used as the conductive phase, and the two can be tightly sintered by high temperature and high pressure technology to form a superhard conductive diamond-nickel composite material. Diamond plays a role in improving the hardness of the composite material as a base phase in the composite material, and nickel plays a role as a conductive path in the composite material as a conductive phase in the composite material. The diffusion rate of nickel atoms in graphite is higher than that of diamond, so that nickel atoms diffuse in the graphite layer between the diamond particles. Afterwards, the graphite between the diamond layers is quickly converted into diamond by ultra-high pressure, so that the nickel is localized between the diamond particles. In addition, due to the high lattice matching degree of diamond and nickel, the conversion of graphite into diamond will be accelerated, the area of ​​the conductive phase in the composite material will be expanded, and the conductivity will be improved. At the same time, nickel can reduce the sintering temperature of nano-diamond as an adhesive. The invention solves the problem that traditional conductive materials have low hardness and superhard materials have poor conductivity. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 This is the morphology of the purchased nickel foam.

[0017] Figure 2 This is the optical morphology of the pre-pressed sample in Example 1.

[0018] Figure 3 This is the XRD pattern of the sample of Example 1.

[0019] Figure 4 This is the Vickers hardness test diagram of the sample in Example 1.

[0020] Figure 5 This is the optical morphology of the pre-pressed sample of Example 2.

[0021] Figure 6 This is the XRD pattern of the sample in Example 2.

[0022] Figure 7 This is the Vickers hardness test diagram of the sample in Example 2.

[0023] Figure 8 The scanning electron microscope morphology of the sample in Example 2 is shown in FIG.

[0024] Fig. 9 This is the XRD pattern of the sample in Example 3.

[0025] Fig.10 This is the Vickers hardness diagram of the sample in Example 3.

[0026] Fig.11 This is the XRD pattern of the sample in Example 4.

[0027] Fig.12 This is the Vickers hardness diagram of the sample in Example 4. DETAILED DESCRIPTION Example 1

[0028] Sample mixing: Commercially purchased nanodiamond with a particle size of 30-50 nm was used as the base powder, and commercially purchased nickel foam with a diameter of 2 mm, a height of 2 mm, and an average pore size of 150 μm (morphology see Figure 1 ). First, the nickel foam was weighed, and then placed in a solution of diamond and anhydrous ethanol in a mass ratio of 1:10. The mixture was then placed in an ultrasonic cleaner at a frequency of 40 kHz and a temperature of 30 °C for 30 min. The nickel foam filled with diamond was taken out and dried in an oven at 100 °C for 120 min. The mass was weighed after drying. The nickel foam accounted for 5% of the total molar weight of the mixture block.

[0029] Sample pretreatment: The sample was loaded into a six-sided hydraulic press block and treated at 700 °C, 5 GPa, for 20 min, and then unloaded to normal pressure. The optical morphology of the pre-pressed sample is shown in Figure 2 It can be seen that nanodiamonds are evenly filled in the pores of nickel foam.

[0030] Sample preparation: The pretreated sample was placed in a synthetic block and sintered using a Kawaii press at a pressure of 16 GPa and a temperature of 1800 °C for 20 min. After the pressure was released, a sample with a diameter of about 1.5 mm and a height of about 2 mm was obtained. The sample was then subjected to XRD test, Vickers hardness test and Van der Pauw method for resistivity measurement. XRD results are shown in Figure 3 , Vickers hardness results are shown in Figure 4 . X-ray diffraction results show that nanodiamonds do not react with nickel, and the phases are diamond and nickel. Vickers hardness shows that the hardness range of the sample is 60.6-77.5 GPa. Since the precursor treatment temperature does not reach the melting point of metallic nickel and the diamond surface is not graphitized, nickel is enriched, and the hardness is characterized by the hardness range. The resistivity of the sample measured by the Van der Pauw method is 5.88*10 -6 Ω·m. Example 2

[0031] Sample mixing: The mixing method and sample ratio are the same as in Example 1.

[0032] Sample pretreatment: The samples were loaded into a six-sided hydraulic press block and treated at 1800 °C, 5 GPa, for 20 min, and then unloaded to normal pressure. The optical microscopy images are shown in Figure 5 , compared with Example 1, the foamed nickel diffuses.

[0033] Sample preparation: The pretreated sample was placed in a synthetic block and sintered using a Kawaii press at a pressure of 16 GPa and a temperature of 1800 °C for 20 min. After the pressure was released, a sample with a diameter of about 1.5 mm and a height of about 2 mm was obtained. The sample was then subjected to XRD, scanning electron microscopy, Vickers hardness test, and Van der Pauw method for resistivity measurement. XRD results are shown in Figure 6 , Vickers hardness results are shown in Figure 7 The scanning electron microscopy results are shown in Figure 8. X-ray diffraction results show that part of the nickel reacts with diamond to form Ni3C, and the other phases are diamond and nickel. Scanning electron microscopy results show that the skeleton of the nickel foam is refined due to diffusion. Vickers hardness shows that the hardness of the sample is 89.0 GPa. Since the precursor treatment temperature reaches the melting point of metallic nickel and the diamond surface is graphitized, nickel can diffuse along the diamond surface, so the hardness distribution is relatively uniform. The resistivity of the sample measured by the Van der Pauw method is 2.36*10 -6 Ω·m. Example 3

[0034] Sample mixing: The mixing method and sample ratio are the same as in Example 1.

[0035] Sample pretreatment: The sample pretreatment was the same as in Example 2.

[0036] Sample preparation: The pretreated sample was placed in a synthetic block and sintered using a Kawaii press at a pressure of 12 GPa, a temperature of 1800 °C, and a holding time of 20 min. After the pressure was released, a sample with a diameter of about 1.5 mm and a height of about 2 mm was obtained. The sample was then subjected to XRD, Vickers hardness test, and Van der Pauw method for resistivity measurement. XRD results are shown in Fig. 9 , Vickers hardness results are shown in Fig.10 The X-ray diffraction results showed that the nanodiamond and nickel did not react, and the same phases as in Example 1 were diamond and nickel. The Vickers hardness showed that the hardness of the sample was 76.1 GPa. The resistivity of the sample measured by the Van der Pauw method was 1.82*10 -6 Ω·m. Example 4

[0037] Sample mixing: The mixing method and sample ratio are the same as in Example 1.

[0038] Sample pretreatment: The sample pretreatment was the same as in Example 2.

[0039] Sample preparation: The pretreated sample was placed in a synthetic block and sintered using a Kawaii press at a pressure of 20 GPa and a temperature of 1800 °C for 20 min. After the pressure was released, a sample with a diameter of about 1 mm and a height of about 1.5 mm was obtained. The sample was then subjected to XRD, Vickers hardness test, and Van der Pauw method for resistivity measurement. The XRD results are shown in Fig.11 , Vickers hardness results are shown in Fig.12 The X-ray diffraction results showed that the nanodiamond and nickel did not react, and the same phases as in Example 1 were diamond and nickel. The Vickers hardness showed that the hardness of the sample was 90.8 GPa, and the resistivity of the sample measured by the Van der Pauw method was 5.63*10 -6 Ω·m.

[0040] In summary, the present invention uses foam composite nanodiamonds and combines high temperature and high pressure to prepare a metallic-level conductive superhard composite metamaterial. Figure 1 As shown, nickel foam is composed of a three-dimensional nickel skeleton and has pores inside that are sufficient to fill diamonds. The results after filling are as follows Figure 2 As shown in Figure 1, it can be observed that the grid-like nickel is embedded in the diamond and interconnected. After the high temperature and high pressure experiment on the sample diamond, its phase structure at the experimental pressure of 16GPa is diamond, nickel carbide and nickel, as shown in Figure 1. Figure 6 As shown; but at other pressures, its phase composition is diamond and nickel, such as Figure 3 , 9 , 11. It can be seen that the metal-grade superhard conductive material prepared by the present invention fills the gap in this field. At the same time, the effective regulation of the microstructure and macroscopic performance of the present invention provides an experimental basis for the design of high-performance composite materials.

Claims

1. A method for preparing a metallic-grade conductive diamond-nickel superhard material, comprising the following steps: 1) Ingredients: First weigh the nickel foam, then put the nano-diamond with a particle size of 30-50 nm and the nickel foam with a diameter of 2 mm and an average pore size of 150 μm into anhydrous ethanol for ultrasonic mixing to obtain a nickel foam mixed block filled with diamond; wherein, The molar ratio of nanodiamond is 93-97%, and the balance is nickel foam; the mass ratio of nanodiamond to anhydrous ethanol is 1:9; the ultrasonic frequency is 40 kHz and the ultrasonic time is 30 min; 2) Drying treatment: Place the nickel foam filled with nanodiamonds with a diameter of 2 mm in a drying oven and dry it at 100 °C for 120 min to remove the anhydrous ethanol, and then weigh it; 3) Pre-pressing treatment: the dried nickel foam is placed in an assembly block, and then placed in a six-sided hydraulic press for pre-pressing at a pressure of 5 GPa, a temperature of 700 ℃ to 2000 ℃, and a holding time of 20 min, and then the pressure is released to obtain a pre-pressed sample with a diameter of 1.5 mm and a height of 2 mm; 4) Sample preparation: The pre-pressed sample was placed in a Kawaii 68 press and sintered at a pressure of 10-20 GPa and a temperature of 1800°C for 20 min. The sample was then cooled and depressurized to obtain a metallic-grade conductive diamond-nickel superhard material.

2. The method for preparing a metallic-grade conductive diamond-nickel superhard material according to claim 1, characterized in that: In the diamond-filled nickel foam mixed block described in step 1), the nickel foam accounts for 5% of the total sample molar weight.

3. The method for preparing a metallic-grade conductive diamond-nickel superhard material according to claim 1, characterized in that: The pre-pressing treatment conditions in step 3) are 5 GPa, 1800°C, and 20 min. The diamond surface is graphitized by the pre-pressing treatment, and nickel diffuses into the graphite, thereby obtaining a pre-pressed sample having a structure of diamond / graphite / nickel from the inside to the outside.

Citation Information

Patent Citations

  • A high-temperature oxidation-resistant and conductive superhard composite material and its preparation method

    CN114231817B

  • Surface-graphitized micro-diamond loaded perovskite composite and preparation method

    CN106423177A

  • Preparation method of composite material and composite material

    CN115637345A